ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA TERHADAP PEMBELAJARAN HYPOTHETICO-DEDUCTIVE REASONING DALAM LEARNING CYCLE 7E - Alfin, Muhammad Babun; Hidayati, Yunin; Hadi, Wiwin Puspita; Rosidi, Irsad (Perkumpulan Pendidik IPA Indonesia (PPII), 2019)
This study aims to determine the effect of the Hypothetico-Deductive Reasoning method in Learning Cycle 7E on students' critical thinking skills. The design of this study is quasi-experimental with nonequivalent control group design and implemented at SMPN 1 Baureno with a population of all class VII. The sample used was 2 classes, namely class VII A as an experimental class and class VII B as a control class. The critical thinking ability test consist of 7 essay questions. It can be concluded that students' critical thinking skills are in good criteria with an average percentage of 72.61%.